Numerical simulation of blasting in confined fractured rocks using an immersed-body fluid-solid interaction model. (April 2020) - Yang, Pan; Lei, Qinghua; Xiang, Jiansheng; Latham, John-Paul; Pain, Christopher
Highlights: We present a fluid-solid interaction model for simulating blast in fractured rocks. The presence of natural fractures significantly affects blast-driven fragmentation. A transition from radial cracking to fracture coalescence dominated regimes is shown. Abstract: We model blast-induced fracturing and fragmentation processes in fractured rocks using a fully coupled fluid-solid interaction model. This model links a finite-discrete element solid solver with a control volume-finite element fluid solver through an immersed-body method. The solid simulator can capture the deformation of intact rocks, interaction of matrix blocks, displacement of existing fractures and propagation of new cracks. The fluid simulator can simulate the highly compressible gas flow involved in the blasting and explosion process, which is assumed to follow the John-Wilkins-Lee equation of state. We design numerical experiments as follows. First, we generate a series of 1 m × 1 m discrete fracture networks associated with different fracture density and mean length values to consider various scenarios of distributed pre-existing fractures in rock. We apply isotropic/anisotropic in-situ stresses to the rock such that the system reaches an equilibrium state. Then we release the compressible gas associated with a prescribed high pressure in the borehole to simulate explosion, which engenders stress wave propagation and new crack generation in the system. We observe that the presence of natural fractures has a significant impact on the blast behaviour of fractured rocks such that new cracks tend to be arrested by pre-existing discontinuities which however accommodate wing cracks at their tips linking with other structures. Blast-driven cracks attempt to propagate along the maximum principal stress direction if an anisotropic stress condition is imposed. Our research findings have important implications for the design and assessment of blasting for underground excavation in fractured formations.